ЦІННІСНІ ОРІЄНТИРИ ВИВЧЕННЯ УКРАЇНСЬКОЇ МУЗИЧНО-ПЕДАГОГІЧНОЇ СПАДЩИНИ (Педагогіка вищої та середньої школи, 2007)
The article covers theoretical and methodological aspects of implementation of the motivational component of mastering musical and pedagogical sources of the past in pedagogical universities and represents the most effective forms and methods of students’ educational and professional activity during the pedagogical practical training.